PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR BPJS KESEHATAN CABANG PALU - ARMANSYAH, ANDI (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
This study aims to determine the effect of compensation and Discipline Work either simultaneously or partially on the Performance of BPJS Health Office Employee Branch Palu. The independent variables used in this study are compensation and Work Discipline. While the dependent variable is Performance. The method used in this research is quantitative descriptive method. The type of research conducted is replication research. The sample was 36 respondents with sampling technique of saturated sample method. Data analysis method used in this study is multiple linear regression analysis method using spss 21. The results of this study indicate that simultaneously compensation and Work Discipline have a significant effect on Employee Performance Office BPJS Health Branch Palu. And partially compensation and work discipline have a significant effect on the performance of employees BPJS Branch Office Health Palu.